2023
DOI: 10.3389/fpubh.2022.1080678
|View full text |Cite
|
Sign up to set email alerts
|

Country score tool to assess readiness and guide evidence generation of immunization programs in aging adults in Europe

Abstract: ObjectivesDelaying of policies for immunization of aging adults, low vaccine uptake, and the lack of supportive evidence at the national level could diminish the value in health and economics of such programs. This study aims to develop a “country score tool” to assess readiness and to facilitate evidence generation for aging adult immunization programs in Europe, and examine the comprehensiveness, relevance, acceptability, and feasibility of the tool.MethodsThe tool was developed in two phases. First, a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…72 73 This theme frequently emerged across guidance documents, where there was often a focus on reaching vulnerable populations, such as children, 57 pregnant women 35 and older adults. 48 Although vaccination equity is recognised as an important aspect for consideration when deploying new vaccines or improving the uptake of underutilised vaccines, specific systems and processes for establishing equity are often not readily available. 74 While the importance of vaccination equity is well recognised, this knowledge does not necessarily translate into practical steps to ensure that people who are underserved by immunisation programmes are adequately provided for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 73 This theme frequently emerged across guidance documents, where there was often a focus on reaching vulnerable populations, such as children, 57 pregnant women 35 and older adults. 48 Although vaccination equity is recognised as an important aspect for consideration when deploying new vaccines or improving the uptake of underutilised vaccines, specific systems and processes for establishing equity are often not readily available. 74 While the importance of vaccination equity is well recognised, this knowledge does not necessarily translate into practical steps to ensure that people who are underserved by immunisation programmes are adequately provided for.…”
Section: Discussionmentioning
confidence: 99%
“…CONCLUSION A country's success in supporting new vaccine deployment and vaccine uptake is dependent on the country's readiness. 48 This scoping review has identified numerous guidance documents that aim to identify these factors. Of the 38 texts identified in this review, only 2 30 38 (which were focused on a specific disease (eg, influenza) or population group (eg, pregnant women), respectively) discussed all 12 overarching themes.…”
Section: Continuedmentioning
confidence: 99%